Effects of high-diluted colloidal silica grouting on the behaviour of a liquefiable sand. Issue 4 (8th October 2020) - Ciardi, Giovanni; Bardotti, Roberto; Vannucchi, Giovanni; Madiai, Claudia
Abstract : The effectiveness of colloidal silica (CS) treatment in increasing the liquefaction resistance of sandy soils is by now amply demonstrated. However, the best value of the CS content to achieve high performance, minimising economic cost and impact on buildings and the environment, has not yet been quantified. This paper presents the results of a laboratory study aimed to evaluate the influence of different CS contents on the behaviour of a liquefiable sand. The investigation included direct shear, cyclic triaxial, hydraulic conductivity and oedometer tests. CS contents 0, 2 and 5% (by weight) were used for all tests, except for direct shear tests (CS contents 0 and 2%) and oedometer tests (CS contents 0, 2, 3, 5, 10 and 13%). The test results showed that 2% CS content was enough to increase the soil strength under cyclic and monotonic loading conditions. The hydraulic conductivity of treated soil decreased significantly as CS content increased. Oedometer tests pointed out that the main disadvantage of CS treatment is the soil compressibility increase. On the basis of the obtained results, 2% CS content seems to be recommended because it shows effectiveness and capability to improve the liquefaction resistance of sand while minimising the soil compressibility increase.